Students’ Perceptions of the Teaching of Grammar - Rex Stardy (Journal of English Language and Culture, 2017)
The objective of this research is to investigate the students’ perceptions of the teaching of grammar as there have been numerous debates among researchers about the importance of teaching grammar.  In order to know whose argument is the right one, it is important to compare it with the result of present research. The results of this research have shown that there are several findings that support the theories proposed by some researchers. However, there are also some findings which do not support the theories. Hopefully, this study will be able to give some valuable insights for English teachers about what their students need in learning grammar. Keywords: Perception, Students, Grammar